Body Image Disorders and Cognitive Distortions among Diabetic Amputees - Al-Dalaeen, Anas Saleh (Jordan Journal of Social Sciences, 2023)
The current study aimed to reveal the level of body image disorders and cognitive distortions among diabetic amputees. The study used the descriptive analytical method. The study sample consisted of diabetic amputees in Karak governorate, whose ages ranged between (25-60) years. So, to achieve the objectives of the study, the Shafi’i Scale (2021) was adapted for body image disorder. And the adaptation of the Salah al-Din Scale (2015) for cognitive distortions, and the psychometric properties of the two scales were verified for validity and reliability. A sample of (61) diabetic amputees responded to both scales, and the data were analyzed using appropriate statistical methods. Accordingly, the results indicated that there was an average level of body image disorder and cognitive distortions among the sample members. And there is a positive, statistically significant correlation between body image disorder and cognitive distortions. The results also indicated that there were differences in body image disorder and cognitive distortions among the sample members according to gender and in favor of females who were more affected by body image disorder and cognitive distortions than males. In its conclusion, the study stressed the need to work on reducing body image disorder and cognitive distortions in individuals with diabetes who have amputation.